2012
DOI: 10.1371/journal.pone.0047992
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Muscle Activities from Electrocorticograms in Primary Motor Cortex of Primates

Abstract: Electrocorticography (ECoG) has drawn attention as an effective recording approach for brain-machine interfaces (BMI). Previous studies have succeeded in classifying movement intention and predicting hand trajectories from ECoG. Despite such successes, however, there still remains considerable work for the realization of ECoG-based BMIs as neuroprosthetics. We developed a method to predict multiple muscle activities from ECoG measurements. We also verified that ECoG signals are effective for predicting muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 55 publications
7
59
0
Order By: Relevance
“…Within primary motor area, however, we could not find experimental evidences to explain the most effective site for force prediction according to anatomical knowledge. Our results just found that ECoG signals from the lateral areas and near areas of CS showed greater efficacy in prediction [33,36]. It might be needed the micro-sized ECoG electrode to find the most effective location within primary motor area.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Within primary motor area, however, we could not find experimental evidences to explain the most effective site for force prediction according to anatomical knowledge. Our results just found that ECoG signals from the lateral areas and near areas of CS showed greater efficacy in prediction [33,36]. It might be needed the micro-sized ECoG electrode to find the most effective location within primary motor area.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, decoding muscle activities are key components for realizing neuro-prosthesis capable of the interaction with environments. We verified that ECoG signals are effective for predicting muscle activities in time varying series when performing sequential movements [36]. We used sparse linear regression to find the best fit between frequency bands of ECoG and electromyographic activity.…”
Section: Decoding Of Muscle Activities From Ecog Signalsmentioning
confidence: 78%
See 3 more Smart Citations